1992
DOI: 10.1149/1.2069303
|View full text |Cite
|
Sign up to set email alerts
|

Deep Ultraviolet Photoresist Based on Tungsten Polyoxometalates and Poly(Vinyl Alcohol) for Bilayer Photolithography

Abstract: A negative tone deep ultraviolet resist, a mixture of phosphotungstic acid and poly(vinyl alcohol) is described. This resist has <100 mJ cm -2 sensitivity and resolves -<0.3 ~m features. Even though the photochemistry involves chemical amplification, the exposed patterns are stable and the process tolerates hours between the exposure and the post-bake steps. The resist is spun from an aqueous solution, and its wet processing is also aqueous. This resist is used in a bilayer scheme, where advantage is taken of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
8

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 5 publications
2
15
0
8
Order By: Relevance
“…In this work, the creation of a stable, non-water-soluble PVA layer onto the polymer coated silicon wafer was pursuit through cross-linking of PVA molecules after their deposition as a thin film onto the surface. The proposed approach for PVA crosslinking is based on the modification of a photolithographic process reported in the past for either deep ultraviolet (DUV) lithography 31 or the formation of metallic features by exploiting the presence of a polyoxometalate used as a photo-oxidation catalyst. 36 The cross-linking of PVA is initiated by the photoreduction of ammonium 18-tungtodiphosphate (Supporting Information scheme 1) or the photoreduction of 12-tungstophosphoric acid, commonly known as phosphotungstic acid, (Supporting Information scheme 2a), 37 which results in partial oxidation of the hydroxyl groups in the PVA molecules to carbonyls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, the creation of a stable, non-water-soluble PVA layer onto the polymer coated silicon wafer was pursuit through cross-linking of PVA molecules after their deposition as a thin film onto the surface. The proposed approach for PVA crosslinking is based on the modification of a photolithographic process reported in the past for either deep ultraviolet (DUV) lithography 31 or the formation of metallic features by exploiting the presence of a polyoxometalate used as a photo-oxidation catalyst. 36 The cross-linking of PVA is initiated by the photoreduction of ammonium 18-tungtodiphosphate (Supporting Information scheme 1) or the photoreduction of 12-tungstophosphoric acid, commonly known as phosphotungstic acid, (Supporting Information scheme 2a), 37 which results in partial oxidation of the hydroxyl groups in the PVA molecules to carbonyls.…”
Section: Resultsmentioning
confidence: 99%
“…36 The cross-linking of PVA is initiated by the photoreduction of ammonium 18-tungtodiphosphate (Supporting Information scheme 1) or the photoreduction of 12-tungstophosphoric acid, commonly known as phosphotungstic acid, (Supporting Information scheme 2a), 37 which results in partial oxidation of the hydroxyl groups in the PVA molecules to carbonyls. Then, the PVA chains undergo dehydration during the postexposure bake and the products are condensed by Diels−Alder reactions during the same step to create a crosslinked PVA/12-tungstophosphoric acid film (Supporting Information scheme 2b) 31 or a cross-linked PVA/ammonium 18-tungtodiphosphate film, correspondingly. The formation of dienes and dienophiles during the postexposure bake can be monitored by UV spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter occurs when poly(acrylamide) transfers a proton to the bridged oxygen in the excited HPW anion (WeO b eW) [13] to form a radical that starts the chain propagation and crosslinking reactions. Similarly, Carls et al [14] observed that combining poly(vinyl alcohol), PVA, with HPW resulted in a hybrid material with photoresist properties, although a photoredox mechanism was claimed for layer-by-layer films with PVA/Dawsontype phosphotungstates/poly(allylamine hydrochloride), PAH [15]. These reports indicate the importance of both the organic functionalities and the self-assembly process in determining the photochromic response of such versatile photoactive materials.…”
Section: Introductionmentioning
confidence: 99%